COLORIMETRIC DETERMINATION OF PARACETAMOL IN RAW MATERIAL AND IN PHARMACEUTICAL DOSAGE FORMS - Usifoh, C O; Adelusi, S A; Adebambo, R F (Biological Sciences - PJSIR, 2002)
A rapid , accurate and simple method is proposed for the determination of p-acetaminophen (paracetamol) in raw material, tablets and syrups. The method is based on measuring the i ntensity of the yellow color that developed when acute acetaminophen is allowed to react with p-dimethylaminobenzaldehyde in 2M I-IC! after heating. The color which absorbs in the visible region oft,450nm is stable for several hours and the intensity is directly proportional to the concentration of the drug, that is, Beer-lambert law is obeyed. The method can be used to analyse paracetamol in raw material and in pharmaceutic al dosage forms.